Features of Risk Stratification, Diagnosis and Secondary Prevention in Patients with Multifocal Arterial Disease. Part 1: Risk Stratification and Diagnosis - V. G. Grachev; S. S. Vedenskaya; O. G. Smolenskaya (Рациональная фармакотерапия в кардиологии, 2021)
Multifocal arterial disease is common in patients with atherosclerotic cardiovascular disease and is associated with an increased risk of cardiovascular complications and death. The possibility of improving the prognosis of patients with multifocal arterial disease is associated with a more efficient diagnosis of both the underlying disease and obstructive atherosclerotic lesions of other localizations and with a more intensive secondary prevention. According to observational studies, the presence of significant stenoses of the carotid arteries and, especially, lower extremities arterial disease can be predictorы of similar lesions in other vascular beds and their detection with screening methods available in clinical practice allows improvement of the diagnosis in patients with suspected coronary artery disease. On the other hand, screening of lower extremities artery diseases in patients with acute coronary syndrome can clarify indications for the use of invasive diagnostic and treatment strategy, in patients with chronic coronary artery disease it can justify more aggressive approaches to secondary prevention.